Doctor to patient communication and patient-satisfaction in a first level of care center in metropolitan Lima, Peru - Domínguez-Samamés, Rafael (2022)
Objective: to evaluate the doctor to patient communication and consumer satisfaction in a first level of care center in metropolitan Lina, Peru. Methods: cross-sectional study that involved 121 participants selected from the outpatient internal medicine service. Two instruments were applied; communication subscale IPC-18 and patient-satisfaction through PSQ-18. Results: 68.6% of participants were females and 66.1% had completed secondary school. Doctor- patient communication was deficient in 39.7% and patient-satisfaction was low at 53.7%. Statistical association between doctor-patient communication and patient-satisfaction (p<0.005). Conclusions: in this first level of care center the doctor-patient communication and patient-satisfaction were suboptimal. More studies are needed in this field.